Principal Managerial Strategies for Enhancing Teachers’ Digital Readiness at SMP Negeri 1 Cimanggu - Ida Mahardika (Lentera Ilmu Nusantara, 2026)
This study aims to analyze the managerial strategies employed by the principal of SMP Negeri 1 Cimanggu to enhance teachers’ digital competence and readiness for technology-based learning. A qualitative case study approach was adopted, involving six key informants selected through purposive sampling, consisting of the principal, the vice principal for curriculum, and representatives of senior and younger teachers. Data were collected through semi-structured interviews, direct observations, and document analysis and were analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The findings indicate that the principal’s managerial strategies were implemented through four main functions: planning digital infrastructure and budget allocation, organizing an information technology team and cross-generational peer coaching, conducting differentiated digital training based on teachers’ competency levels, and implementing periodic technology-based supervision. These strategies helped reduce technostress among senior teachers, improve teachers’ confidence and technical readiness, and encourage the use of interactive digital platforms in classroom learning. The study highlights that teachers’ digital readiness is influenced not only by individual technological competence but also by adaptive, supportive, and well-structured school leadership. The findings imply that school principals should integrate infrastructure development, differentiated training, peer assistance, and continuous supervision to support sustainable digital transformation in schools.